Cancer Drug Targeting: Molecular Mechanism, Approaches, and Regulatory Framework - Chandel, Rushikesh Somnath; Dewangan, Hitesh Kumar (Current Pharmaceutical Design, 2025)
Novel vaccine formulations called nano vaccines which use nanoparticles (NPs) as adjuvants or carriers, are being developed in place of conventional vaccines. The field of study on peptide-based nano vaccines is enlarging fast as a result of combining antigenic peptides with nano-transport systems. This paper explores advancements in anticancer nano vaccines, focusing on their mechanisms, challenges, and opportunities. It discusses peptide nano vaccines, personalized vaccines, cancer prevention strategies, clinical translation, and self-assembling multivalent nanovaccines. It also discusses nanocarriers' role in delivering tumor-associated antigens and immune-stimulatory adjuvants. In 2024, the American Cancer Society projects over 2 million new cancer cases in the United States, marking the first year this milestone has been surpassed. This equates to approximately 5,480 new cancer diagnoses daily. Additionally, over 611,000 cancer-related deaths are expected, which translates to more than 1,600 deaths per day. The National Centre for Health Statistics mentions the mortality data also shows the various types of cancer percentages. This guideline provides comprehensive recommendations for sponsors submitting a novel drug under Investigation use of curative cancer vaccinations, focusing on safety, effectiveness, dosage optimization, adjuvant use, patient group selection, immune response monitoring, biomarker evaluation, multi-antigen vaccine development, phase-specific difficulties, non-clinical testing, and legal frameworks, while also referencing relevant legal foundations and recommendations.
Keywords: peptide